2020
DOI: 10.1302/2633-1462.111.bjo-2020-0012.r1
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus 'all-inside' anterior cruciate ligament reconstruction: a randomized controlled trial comparing hamstring strength and functional outcome

Abstract: Cite this article: Bone Joint Open 2020;1-11:706–708.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Reconstructive techniques have evolved during the past 60 years through anteromedial bundle reconstruction, double-bundle reconstruction, and an 'all-inside' technique, to more recent biological or synthetic augmentation with preservation of the ACL remnant. 1,[18][19][20][21][22] Computer-assisted navigation in ACL reconstruction, with the aim of improving the position of the tunnels and improving rotatory stability, is a goal for some techniques. 23,24 These have helped patients to regain a stable knee and return to sports.…”
Section: Is the Die Cast? Anterior Cruciate Ligament Injury And Osteo...mentioning
confidence: 99%
“…Reconstructive techniques have evolved during the past 60 years through anteromedial bundle reconstruction, double-bundle reconstruction, and an 'all-inside' technique, to more recent biological or synthetic augmentation with preservation of the ACL remnant. 1,[18][19][20][21][22] Computer-assisted navigation in ACL reconstruction, with the aim of improving the position of the tunnels and improving rotatory stability, is a goal for some techniques. 23,24 These have helped patients to regain a stable knee and return to sports.…”
Section: Is the Die Cast? Anterior Cruciate Ligament Injury And Osteo...mentioning
confidence: 99%
“…Recent single-surgeon comparison research indicated that the strength of the knee with all-inside ACL restoration was superior, but the functional result was comparable. 8 The all-inside ACL reconstruction with an ST4 autograft and cortical button fixation on both ends is a viable alternative to the conventional technique. 9 Before tensioning, the graft of the all-inside technique should be 50 to 70 mm long, with a maximum length of 75 mm after tensioning.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…The all-inside technique (AIT) for anterior cruciate ligament reconstruction is gaining popularity as a more anatomic, less invasive technique with the potential for more rapid recovery. This systematic review aims to critically assess components of the technique its safety profile, outcomes and complications 7 . The goal of the all-inside method is to minimize surgical trauma.…”
Section: Introductionmentioning
confidence: 99%